Pengaruh Reduksi Terhadap Laju Korosi Baja Karbon Rendah Pada Temperature Operasi Berbeda - Perpustakaan UGM, i-lib ([Yogyakarta] : Faculty of geografi Gadjah Mada University, 1997)
Corrosion resistance of metal alloys depend on the manufacturing processes. Corrosion rate of metal alloys can be measured by metallographic method and polarization method. In this research polarization test is used to determine corrosion potensials and current densities of cold rolled low carbon steel with e : 10%, 20%, 30%, 40%, 50% and with medium temperature: ambient temperature, 30°C, 40°C, 50°C, 60°C, 70°C. The current densities then converted into corrosion rates. For examples, corrosion rates (mpy): CR1(50%,ambient temperature)= 19,068